Covid-19 Implications to Transatlantic Security - Jakštaitė-Confortola, Gerda (Politologija, 2024)
Although there were many disagreements in transatlantic relations before the COVIC-19, the pandemic accelerated tensions in transatlantic relations even more. The inauguration of the new US president Joe Biden, however, has been perceived as a new chapter in transatlantic relations. The paper aims to assess the COVID-19 pandemic implications to transatlantic relations and answer the question of whether the pandemic has strengthened or weakened the transatlantic security community? The paper stems from the idea that transatlantic countries compose a transatlantic security community. It examines the COVID-19 implications to several tiers of features that should be present in every security community: namely, implications to the perception of threats, patterns of communication and policy coordination, as well as to institutional framework. The paper argues that COVID-19 has not transformed the transatlantic security community; however, it highlighted certain problematic aspects of transatlantic relations.
Keywords: Transatlantic relations; COVID-19; Security Community; United States; European Union